2001
DOI: 10.1123/jab.17.1.43
|View full text |Cite
|
Sign up to set email alerts
|

Sources of Error in Determining Countermovement Jump Height with the Impulse Method

Abstract: A comprehensive error analysis was performed on the impulse method. To evaluate the potential errors, jump height was recalculated after alteringoneof the measurement or calculation techniquaes while leaving the others unchanged, and then comparing it to the reference jump height (best estimate of true jump height). Measurement techniques introduced the greatest error. Low-pass filters with cutoff frequencies < 580 Hz led to systematic underestimations of jump height, ≤26%. Low sampling frequencies (<1,0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
121
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(127 citation statements)
references
References 5 publications
1
121
0
5
Order By: Relevance
“…Then, the force-time curve was integrated by using the Trapezoidal method from a point prior to the initiation of the counter movement to the point of take-off (Feltner et al, 2004;Hanson et al, 2007;Linthorne, 2001;Moir, 2008;Street et al, 2001). Alternative net impulse was calculated as the isolated area under a force-time curve (Figure 1).…”
Section: Variable Measurements and Calculationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, the force-time curve was integrated by using the Trapezoidal method from a point prior to the initiation of the counter movement to the point of take-off (Feltner et al, 2004;Hanson et al, 2007;Linthorne, 2001;Moir, 2008;Street et al, 2001). Alternative net impulse was calculated as the isolated area under a force-time curve (Figure 1).…”
Section: Variable Measurements and Calculationsmentioning
confidence: 99%
“…Mizuguchi et al (Feltner et al, 2004;Hanson et al, 2007;Linthorne, 2001;Moir, 2008;Street, McMillan, Board, Rasmussen, & Heneghan, 2001). However, the integration of an entire force-time curve makes it impossible to identify what portion of a CMJ force-time curve represents net impulse.…”
mentioning
confidence: 95%
“…Using a forward dynamics approach, the force data were integrated to calculate velocity and displacement. The guidelines of Street et al (24) were used, which have been shown to allow for the most valid calculation of the JH.…”
Section: Jump Testing Data Analysismentioning
confidence: 99%
“…After collection, the vertical component of the ground reaction force (GRF) time history was exported to a custom-built excel sheet for analysis. Body mass, jump start time, and take off were calculated using methods previously described (42).…”
Section: Neuromuscular Performancementioning
confidence: 99%